1998
DOI: 10.1016/s0735-1097(98)00492-6
|View full text |Cite
|
Sign up to set email alerts
|

Acute hemodynamic effects of biventricular DDD pacing in patients with end-stage heart failure

Abstract: This acute hemodynamic study demonstrated that biventricular DDD pacing may significantly improve cardiac performance in patients with IVCB and with severe heart failure, in comparison with intrinsic conduction and single-site RV DDD pacing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
230
2
17

Year Published

2000
2000
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 470 publications
(261 citation statements)
references
References 21 publications
8
230
2
17
Order By: Relevance
“…17,18 Such observations have suggested that patients with DCM and basal discoordination might benefit from LV or biventricular VDD pacing, and this was recently confirmed. [2][3][4][5] However, the response magnitude varies, highlighting the importance of identifying responsive individuals. 6 The present study is the first to systematically test potential markers of clinical response to pacing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 Such observations have suggested that patients with DCM and basal discoordination might benefit from LV or biventricular VDD pacing, and this was recently confirmed. [2][3][4][5] However, the response magnitude varies, highlighting the importance of identifying responsive individuals. 6 The present study is the first to systematically test potential markers of clinical response to pacing.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] By providing early stimulation to the otherwise late-activated region, pacing probably improves contractile coordination to enhance ejection. However, the therapy involves an implantable device, making it important to identify patients most likely to benefit.…”
mentioning
confidence: 99%
“…1,2 Such patients frequently have marked mechanical dyssynchrony that is improved by biventricular pacing, 3,4 which augments left ventricular (LV) contractile function. 5,6 Short atrioventricular delay pacing may also reduce presystolic mitral regurgitation.…”
mentioning
confidence: 99%
“…1 It has been recently shown that correcting this condition by biventricular pacing cardiac resynchronization therapy (CRT) could improve NYHA stage, life quality, oxygen uptake, cardiac diameters, ejection fraction, and even prognosis. 2 -4 Central hemodynamics also were shown to improve in acute testings, 5 but no data have been published till now on their long-term course using repeated right heart catheterization.…”
Section: Introductionmentioning
confidence: 99%